Find the value of for which .
( denotes the first derivative of with respect to .)
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Multiply both sides of the given equation by e − x : e − x f ( x ) = ∫ 0 x e − y f ′ ( y ) d y − ( x 2 − x + 1 )
Differentiate both sides with respect to x : e − x f ′ ( x ) − e − x f ( x ) = e − x f ′ ( x ) − ( 2 x − 1 )
Solve for f ( x ) : f ( x ) = ( 2 x − 1 ) e x which equals zero when 2 x − 1 = 0 ⟺ x = 2 1